RNA IN CYTOPLASMIC AND NUCLEAR FRACTIONS OF CELLULAR SLIME MOLD AMEBAS - Cocucci, S. M. (The Rockefeller University Press, 1970)
A method is described for the rapid separation of cellular slime mold (Dictyostelium discoideum) cells into nuclear and cytoplasmic fractions. Sucrose density sedimentation profiles of radioactivity from cells that had been grown for long or short periods in the presence of uridine-(3)H indicate very low levels of cross-contamination between the fractions. The nuclear fraction contains few, if any, ribosomes. In exponentially growing cells, at least 80% of the ribosomes were associated in polysomal complexes. No loss of counts from pre-labeled rRNA was observed during 2 generations (24 hr) of logarithmic growth and, within the polysomal complexes, the distributions of the preformed material and of rRNA synthesized during the 2 generations were identical. In stationary phase cells that had entered the developmental program leading to fruiting body construction, the rRNA turned over rapidly so that by the end of development at least 75% of the ribosomes fabricated during exponential growth had disappeared and had been replaced by new ones synthesized during the morphogenetic sequence. The preformed ribosomes disappeared preferentially from the monosomal contingent; the newly synthesized ribosomes appeared exclusively in the polysomal contingent and did not appear as monosomes in appreciable numbers for at least 6 hr. The possible significance of this wholesale replacement of ribosomes is discussed.